Severe reflux esophagitis after total gastrectomy successfully treated by transposition of the jejunojejunal anastomosis: a report of two cases - Noriyuki Nishiwaki; Shinji Hato; Tetsuya Kagawa; Tomokazu Kakishita; Isao Nozaki (Surgical Case Reports)
Abstract Background Reflux esophagitis after total gastrectomy is often difficult to treat. In this report, we describe two cases of reflux esophagitis that were refractory to medical therapy and successfully treated by transposition of the jejunojejunal anastomosis. Case presentation Case 1: A 66-year-old man underwent total gastrectomy and cholecystectomy for gastric cancer, and Roux-en-Y (RY) reconstruction was performed. The pathological diagnosis was T4aN3aM0 stage IIIC. Five months later, esophagogastroduodenoscopy identified reflux esophagitis. Although he was treated with various oral medications and was hospitalized six times, he lost 19 kg of weight. Finally, the patient was reoperated 3 years postoperatively. Intraoperative findings showed that there was no evidence of recurrence or severe adhesions that could have caused obstruction, and the anastomotic distance between the esophagojejunostomy and the jejunojejunostomy was approximately 40 cm. The jejunojejunostomy was re-anastomosed to increase the distance to 100 cm. Two years and 6 months after the reoperation, there was no recurrence of reflux esophagitis, and the patient’s weight increased by 14 kg. Case 2: A 68-year-old woman underwent total gastrectomy and cholecystectomy for gastric cancer, and RY reconstruction was performed. The pathological diagnosis was T4aN0M0 stage IIB. Similar to Case 1, the patient was diagnosed with reflux esophagitis 5 months later. She lost 23 kg of weight and was reoperated at 6 months postoperatively. Intraoperative findings showed that there was no evidence of recurrence or severe adhesions, and transposition of the jejunojejunostomy was performed to increase the distance between anastomoses from 40 to 100 cm. Two years and 8 months after the reoperation, there was no recurrence of reflux esophagitis, and her weight increased by 15 kg. Conclusions Transposition of the jejunojejunostomy was an effective treatment for medication-resistant severe reflux esophagitis after total gastrectomy.